Enhanced metal bioleaching mechanisms of extracellular polymeric substance for obsolete LiNixCoyMn1-x-yO2 at high pulp density. (15th September 2022) - Wang, Jia; Cui, Yanchao; Chu, Huichao; Tian, Bingyang; Li, Huimin; Zhang, Mingshun; Xin, Baoping
Abstract: Harmful chemicals present in electric vehicle Li-ion batteries (EV LIBs) can limit the pulp density of bioleaching processes using Acidithiobacillus sp. to 1.0% (w/v) or lower. The strong enhancing mechanisms of extracellular polymeric substances (EPS) on the bioleaching of metals from spent EV LIBs at high pulp density (4% w/v) were studied using bio-chemical, spectroscopic, surface structure imaging and bioleaching kinetic methods. Results demonstrated that the added EPS significantly improved bioleaching efficiency of Ni, Co and Mn improved by 42%, 40% and 44%, respectively. EPS addition boosted the growth of cells under adverse conditions to produce more biogenic H + while Fe 3+ and Fe 2+ were adsorbed by the biopolymer. This increased Li extraction by acid dissolution and concentrated the Fe 3+ /Fe 2+ cycle via non-contact mechanisms for the subsequent contact bioleaching of Ni, CO and Mn at the EV LIB-bacteria interface. During the leaching process, added EPS improved adhesion of the bacterial cells to the EV LIBs, and the resultant strong interfacial reactions promoted bioleaching of the target metals. Hence, a combination of non-contact and contact mechanisms initiated by the addition of EPS enhanced the bioleaching of spent EV LIBs at high pulp density. Graphical abstract: Image 1 Highlights: Added EPS greatly improve bioleaching yield of spent EV LIBs at pulp density of 4%. Added EPS boost resistance of cell to toxic chemical to produce more H + and Fe 3+ /Fe 2+ . Added EPS enhance cell adhesion and oxidation. EPS increased the interface reaction in favor of leaching. There is a significant positive correlation between the dissolution efficiency of metals and the concentration of EPS.